Anxiety increases breakthrough of threat stimuli in continuous flash suppression. - Capitão, L; Underdown, S; Vile, S; Yang, E; Harmer, C; Murphy, SE (American Psychological Association Inc., 2014)
Trait anxiety is associated with an excessive processing of danger-related stimuli, predisposing individuals to quickly detect threatening cues. Early, automatic mechanisms are believed to be responsible for the production of these cognitive biases; however, limitations in the paradigms most commonly used to achieve visual suppression or attentional unawareness have left open the possibility of strategic mechanisms influencing these early stages of information processing. Establishing whether symptoms of anxiety are associated with truly automatic biases in processing is an essential step in determining their etiology and in developing targeted cognitive interventions. We addressed this question using continuous flash suppression (CFS), a novel and robust method of visual suppression capable of rendering a stimulus invisible from awareness for extended durations. We specifically investigated the degree to which trait anxiety influenced the suppression of threatening, positive, and neutral faces. Forty-nine individuals, with no reported history of psychological problems and varying levels of anxiety, were recruited. Higher trait anxiety scores were associated with an increased speed to detect fearful compared with happy faces. These results indicate that the bias toward threatening information associated with symptoms of anxiety operates, at least partly, at an early stage of information processing. This suggests that cognitive interventions for anxiety may benefit from directly targeting such early and potentially preconscious processes.